Characterization of Human Blood Monocytes and Intestinal Macrophages. (13th February 2018) - Dennis, Evida A.; Robinson, Tanya O.; Smythies, Lesley E.; Smith, Phillip D.
Abstract: Monocytes and macrophages play fundamental roles in defense against microbes, clearance of senescent and dead cells, and immunoregulation. Although blood monocytes are the source of intestinal macrophages in the developed mucosal immune system, blood monocytes and intestinal macrophages from healthy human subjects display distinct phenotypic and functional differences. Blood monocytes can be induced to polarize into M1 and M2 macrophages, whereas intestinal macrophages appear to be terminally differentiated and are unable to undergo such inducible polarization. Nevertheless, in response to local conditions, monocytes differentiated into intestinal macrophages display phenotypic and functional characteristics that enhance their capacity to provide non‐inflammatory host defense and participate in local immunoregulation. Using the protocols described here, this unit presents the key phenotypic and functional differences between human blood monocytes and intestinal macrophages, as well as between mouse and human intestinal macrophages. © 2017 by John Wiley & Sons, Inc.